Renegade magic - Burgis, Stephanie (Burgis, Stephanie. Kat, incorrigible (New York, N.Y.), 2013)
Twelve-year-old Kat tries to use her untrained magical powers to prevent use of the wild magic of Sulis Minerva found in Bath, England, where Stepmama has brought the family in hopes of finding Kat's sister a proper match.